Potlačení mechanických vlivů při přenosu optickým vláknem - Pavlů, Michal (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2008)
Práce se zabývá problematikou potlačení mechanických vlivů při přenosu optickým vláknem. V práci je proveden rozbor vlivů, které mají největší vliv na polarizaci v optickém vlákně. Jsou navrženy metody pro zachování polarizace v optickém vlákně. Teoreticky jsou analyzovány metody pro zachování stavu polarizace v optickém vlákně. Vybraná metoda je teoreticky analyzována a experimentálně realizována. Na základě získaných výsledků se tato metoda ukázala jako vhodná pro řešení tohoto problému.

This bachelors project deals with the suppresion of mechanical stress impacts in fiber optic transmission systems. Factors that have major influence on the polarization state distortion in optical fiber are discussed. It has been propřed the utilization of orthoconjugate retroreflector (OKR) for the compensation of polarization state degeneration. The theoretical analysis of this method is performed. The OKR method has been experimentally verified in the fiber optic current sensor. On the basis of results which were obtained by experimental verification the experimental results show evidence konvenience of the designed method.
The suppresion of mechanical stress impacts in fiber optic transmission systems
Keywords: Optovláknový senzor; ohyb optického vlákna; polarizace vlny; Jonesův počet; Faradayův jev; lineární dvojlom; kruhový dvojlom.; Fiber optic sensor; bending of optical fiber; polarization of the optic wave; Jones calculus; Faraday effect; linear birefringence; circular birefringence.